Clinical roles of breast 3T MRI, FDG PET/CT, and breast ultrasound for asymptomatic women with an abnormal screening mammogram. Issue 12 (December 2015) - Chou, Chen‐Pin; Peng, Nan‐Jing; Chang, Tsung‐Hsien; Yang, Tsung‐Lung; Hu, Chin; Lin, Huey‐Shyan; Huang, Jer‐Shyung; Pan, Huay‐Ben
Abstract : Background : Magnetic resonance imaging (MRI) and fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) show promise for molecular cancer imaging. We evaluated 3T MRI, FDG PET/CT, and ultrasound images for asymptomatic women with an abnormal screening mammogram. Methods : The Institutional Review Board of Kaohsiung Veterans General Hospital (Kaohsiung, Taiwan) approved the study. Patients provided written informed consent. A total of 11, 865 screening mammograms of 118, 65 women were performed at our facility between January 2011 and December 2012. Fifty‐three asymptomatic women (mean age, 53.3 years) whose screening mammograms had a Breast Imaging Reporting and Data System (BI‐RADS) category of 4 or 5 were ultimately enrolled in this study. Breast 3T MRI, FDG PET/CT, and breast ultrasound were performed before biopsy. All imaging modalities were compared by lesion‐by‐lesion analyses. Results : Fifty‐nine breast lesions (28 malignant and 31 benign lesions) from 53 women were analyzed. The sensitivity, specificity, and accuracy for 28 breast cancers were 96%, 77%, and 86%, respectively, for breast 3T MRI; 50%, 100%, and 76%, respectively, for FDG PET, CT; and 61%, 87%, and 74%, respectively, for breast ultrasound. One 0.8‐cm invasive breast cancer was missed by the screening mammogram, but detected by breast 3T MRI and FDG PET/CT. The sensitivity for detecting breast cancer was significantly higher with MRI than with PET/CT or ultrasound (for all, p < 0.01). The specificity for detecting breast cancer was significantly higher for PET/CT than for breast MRI ( p = 0.02). The sensitivity exhibited by 3T breast MRI and FDG PET/CT for 16 noninvasive breast cancers was 94% and 25%, respectively. Conclusion : On screening mammograms, breast 3T MRI showed higher sensitivity but less specificity than FDG PET/CT for detecting asymptomatic breast cancers.